Doctor Drone: Non-invasive Measurement of Humpback Whale Vital Signs Using Unoccupied Aerial System Infrared Thermography - Horton, Travis W.; Hauser, Nan; Cassel, Shannon; Klaus, K. Frederika; Fettermann, Ticiana; Key, Nicholas (Frontiers in Marine Science, 2019)
Measuring and monitoring the behavior and biomedical condition of free-ranging whales remains a fundamental challenge in cetacean science and conservation. Advances in unoccupied aerial systems (UAS) and infrared thermography (IRT) create unprecedented opportunities to fill these knowledge gaps and advance our understanding of how cetaceans interact with the environment. Here, we show that non-invasive UAS-IRT systems, deployed from shore-based positions in a humpback whale (Megaptera novaeangliae) calving ground, can be used to document rarely observed whale behaviors and quantify biomedical vital signs. Our findings demonstrate: 1) prolonged (>3 h) logging behavior by a mother-calf pair located ~550 m offshore; 2) that the calf’s respiration rate (~3 breaths per minute) was 6 times higher than its mother’s (~0.5 breaths per minute); 3) that the calf’s blowholes were ~1.55° C warmer than adjacent ocean water and that the mother’s blowholes were ~2.16° C warmer than adjacent ocean water; 4) that the mother’s dorsal fin included four infrared hot-spots, each separated by ~20 cm in horizontal distance, that ranged between 1° C and 2° C warmer than adjacent ocean water; 5) a significant (p<<0.05; wavelet analysis) temporal cyclicity in the hottest of the mother’s dorsal fin hot-spots consistent with cardiovascular blood flow pumped at an apneic heart rate of 9.3 beats per minute. Wider deployment and development of UAS-IRT technologies should help to both overcome current challenges, including cost and data processing, and provide unique perspectives and data that will inform our understanding of whale behavior and biomedical condition in rapidly changing marine systems.